Diseño de guión para circuito “senderos del montubio” dirigido a turistas con discapacidad visual - Rebolledo Cadena, Melanny Elehanara (2021)
The following case study focuses on the design of the script for the “Senderos del montubio” circuit aimed at visually impaired tourists, which responds to the visionary R&D project in the province of Los Ríos. Mobile Application and Digital Guide Senderos del Montubio” from the Technical University of Babahoyo. The methodology of this qualitative research is exploratory, inductive and deductive. A bibliographic review was carried out for data collection and subsequent design of the inputs for the research, which consisted of a crop information sheet and a fish farming file that were applied with the collaboration of key informants in the Self-Sustainable Integral Farm from the Technical University of Babahoyo. The information obtained came to proceed with the elaboration of a structure that served as an instrument for the design of the script for tourists with visual disabilities. To collect information on agrotourism farms, the methodology of the qualitative valuation model of attributes of agrotourism farms was used. With the results of the research, the proposals for audio guides were developed. It is suggested to carry out this type of case study in other latitudes of the country and to continue creating opportunities for the development of inclusive tourism. In addition, it is recommended to establish an inclusive agrotourism script methodology